Life cycle assessment of structural glued laminated timber production with different dimensions and exposure conditions - Katsuyuki Nakano; Nobuaki Hattori; Masahiro Koide; Mai Imago; Yuta Yamada; Takuya Ogawa (Journal of Wood Science)
Abstract Glued laminated timber (glulam) is an essential material in modern wooden constructions that offers advantages in terms of strength and versatility. This study conducted a life cycle assessment (LCA) of glulam production in Japan and analyzed the environmental impacts based on different dimensions and exposure conditions. Primary data were collected from 12 factories representing 58.1% of Japan’s production. The assessment followed the ISO 14040/14044 standards and employed mass-based allocation as the primary approach, with economic allocation analyzed for comparison. The results revealed that the major contributors to greenhouse gas (GHG) emissions from glulam production were purchased lamina manufacturing (38%), transportation (27%), and electricity consumption (21%). Large-dimension glulam exhibited the highest environmental impact, largely due to their increased energy consumption. Despite the differences in adhesive types for various exposure conditions, their impact on overall emissions was relatively minor. A sensitivity analysis of the allocation methods revealed significant variations in the reported emissions, emphasizing the importance of methodological choices in LCA studies. This study provides geographically representative LCA data for glulam production in Japan, thereby contributing to improvements in sustainable manufacturing practices. These findings highlight the need to optimize raw material procurement, decarbonize energy, and improve transport efficiency to reduce environmental impacts. Future research should refine the LCA data quality, particularly for lamina production and international supply chains. These insights can support policy development and industrial efforts toward more environmentally sustainable wood utilization.